Breaking Bad News of Cancer Diagnosis- The Cancer Patients’ Perceptions in Serian District - Gabriel Bain, Mathew (US National Library of Medicine, 2014)
This study aimed to assess the perceptions of breaking bad news of cancer diagnosis as perceived by the cancer patients. The research method used was a cross sectional study on cancer patients in Serian district using Breaking bad news Assessment Schedule (BAS) questionnaire. It was conducted using snowballing sampling among cancer patients in Serian district. Face to face interview was conducted after the consent was obtained. Data was entered and analyzed using SPSS version 19. A total of 134 patients participated in this study. Majority were comfortable with the current method of breaking bad news. The main aspects found were, the importance usage of body language, management of time and identifying patients' key area of concerns. There were significant difference between sex and information giving (p=0.028) and general consideration (p=0.016) and also between age and setting the scene (p=0.042). It also illustrated that there were significant difference between the types of cancer and the setting of scene (p=0.018), breaking bad news techniques (p=0.010), eliciting concerns (p=0.003) and information giving (p=0.004). Good and effective communication skill of breaking bad news is vital to the management of cancer patients. As the incidence of new cases of cancer increase every year, the importance of delivering the bad news becomes more pertinent and essential. Future study also must be conducted to identify which specific aspect of communication should be placed more emphasis according to the perception of Malaysian cancer patients and formal training and guidelines be formulated on our local characteristics and specific factors for cancer patients in Malaysia.